A CAPABILITY-DRIVEN ADAPTIVE ENTERPRISE ARCHITECTURE FRAMEWORK FOR SMART HIGHER EDUCATION ECOSYSTEMS - Syaflan Sandi Harta Putra; Mhd. Adhitiya Okta Riyandi; Haditya Prasetyo (Ensiklopedia of Journal, 2026)
Digital transformation in higher education requires effective integration of academic, learning, administrative, and decision-support services. However, existing Enterprise Architecture (EA) approaches often lack adaptability and capability-oriented mechanisms to support continuous organizational evolution. This study proposes a Capability-Driven Adaptive Enterprise Architecture Framework (CDA-EAF) to support the development of an integrated intelligent higher education ecosystem. The framework is developed using the Design Science Research (DSR) methodology, with TOGAF ADM as the architectural foundation, enhanced through capability-based planning, enterprise integration, and adaptive mechanisms. Validation is conducted through a higher education case study involving expert evaluation and architecture quality assessment. The results demonstrate that the proposed framework improves business–IT alignment, service interoperability, decision-making effectiveness, and organizational adaptability compared to conventional EA approaches. The study contributes a capability-driven adaptive enterprise architecture model that can serve as a reference for universities in developing integrated, sustainable, and smart campus ecosystems that support digital transformation.Keywords: Enterprise Architecture, Adaptive Enterprise Architecture, Capability-Based Planning, Smart Campus, Digital Transformation, Higher Education.